PENGARUH RELAKSASI PROGRESIF TERHADAP PENURUNAN NYERI PADA PASIEN POST OPERASI SECTIO CAESAREA PADA HARI KE 1-2 - Cahyono, Aris Dwi (Akademi Keperawatan Pamenang, 2014)
After Sectio Caesarea surgery has completed and patients are getting conscious and the effect of anesthesia has finished, they will feel pain on body organ where surgery is done. There are two methods to decrease pain scale of Sectio Caesarean surgery namely pharmacology by using medicines and non-pharmacy by using progressive relaxation technique. The purpose of this research is to identify the influence of progressive relaxation to pain decrease to the patients of Sectio Caesarea surgery in Maternal Room of Region General Hospital of Kediri Regency in 2014.Research design was Pre-Post Test Experiment. The observed populations were all patients of post section caesarean surgery in the first and second day namely 38 patients. Sample used purposive sampling and consisted of 9 respondents. Data analysis was implemented by comparing pain scale pre and post intervention and being analyzed as descriptive. Research result showed that pre-intervention, value of mean was 5,66 with standard deviation 1, and post-intervention, value of mean was 4,66 with standard deviation 1,5. Analysis result showed a decrease of mean value namely 1 and standard deviation 0,54. There was influence of progressive relaxation to pain decrease to the patients of Sectio Caesarea surgery in Maternal Room of Region General Hospital of Kediri Regency in 2014. It is hoped for medical staffs to use progressive relaxation technique as one of chosen therapies to decrease pain scale beside of medicines. Keywords : Progressive relaxation, pain, post sectio caesarean surgery.